NONSTEROIDAL ANTI-INFLAMMATORY DRUGS, PHYSICAL EXERCISE AND GINGER SUPPLEMENTATION AS ACCESSIBLE THERAPEUTIC OPTIONS IN THE MANAGEMENT OF PRIMARY DYSMENORRHEA: A LITERATURE REVIEW - Karolina Kananowicz; Patryk Heryć; Zuzanna Kudlińska; Honorata Juniewicz; Ryszard Łagowski; Julia Kosęda; Anna Jędrasiak; Zofia Laska; Marianna Latour; Jakub Piotrowski (International Journal of Innovative Technologies in Social Science, 2025)
Background: Primary dysmenorrhea (PD) constitutes the most prevalent gynecological disorder among women of reproductive age and is associated with a substantial reduction in quality of life and social functioning. While nonsteroidal anti-inflammatory drugs (NSAIDs) remain the first-line treatment due to their proven analgesic efficacy, their use may be limited by the risk of adverse effects. Consequently, increasing scientific attention has been directed toward non-pharmacological alternatives, including physical activity and ginger supplementation, which demonstrate a more favorable safety profile.Aim: The objective of this review is to systematize and evaluate the effectiveness of physical activity, nonsteroidal anti-inflammatory drugs (NSAIDs) and ginger supplementation in the management of primary dysmenorrhea.Material and Methods: A comprehensive literature search in PubMed was conducted. The review covered RCTs, observational studies and meta-analyses on the effects of NSAIDs, exercise and ginger on menstrual pain intensity and duration in women with primary dysmenorrhea.Results: The analysis of current literature indicates that NSAIDs, physical activity and ginger extract each contribute to alleviating pain associated with primary dysmenorrhea. Among the interventions examined, NSAIDs demonstrated the highest short-term analgesic efficacy. Physical exercise provided comparable reductions in pain intensity and duration, with the added benefit of improved psychological well-being. Ginger significantly reduced pain symptoms and showed efficacy comparable to NSAIDs.Conclusions: According to current guidelines, NSAIDs remain the first-line pharmacological treatment for primary dysmenorrhea due to their proven efficacy. However, regular physical activity and ginger supplementation represent safe and effective alternatives, particularly for women who experience adverse effects from NSAID use.